2015
DOI: 10.1111/hsc.12291
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion and intellectual disability: listening to men

Abstract: Taking responsibility for your own health has been a central tenet of public health policy internationally for a number of decades. Governments in the UK and internationally continue to promote a plethora of health promotion strategies, encouraging individuals and communities to adopt healthy lifestyle choices. Although it is widely recognised that men are not as proactive in seeking out medical help or taking on health promotion advice as women, limited gender-sensitive research exists in the field of intelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…There may be transferable evidence from studies involving children and younger people from this population and other cognitive disability populations (for example, patients with dementia, cerebral palsy, stroke, or acquired brain injury). The use of convenience samples 23 , 56 and self-selection 20 may also bias the results. Some studies were limited to urban areas as opposed to rural areas, which may pose different healthcare barriers.…”
Section: Discussionmentioning
confidence: 99%
“…There may be transferable evidence from studies involving children and younger people from this population and other cognitive disability populations (for example, patients with dementia, cerebral palsy, stroke, or acquired brain injury). The use of convenience samples 23 , 56 and self-selection 20 may also bias the results. Some studies were limited to urban areas as opposed to rural areas, which may pose different healthcare barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies reported in 16 publications, published from 2003 to 2017, were included in this group (Table 12). Of these, three dealt with general practice, 44,45,48 three dealt with a range of primary care services, 36,37,49 three dealt with carers working at residential or supported living homes [33][34][35]43 and two dealt with formal and informal carers of people with ID in residential or family homes. 38,39 The other three studies dealt with audiology services, 42 cervical and cancer screening 40 and sexual health.…”
Section: Identifying Needmentioning
confidence: 99%
“…There were 16 papers reporting 14 different studies in this cluster. Among these studies, health needs were identified by the person with ID, 34,36,38,41,44 family carers, 49,114 paid carers 33,35,39,40,42,48,73,114,115 and health professionals. 37,45,48 Identifying health need depends on some knowledge of potential risks to health.…”
Section: Identifying Needmentioning
confidence: 99%
See 2 more Smart Citations